A fungal endophyte induces local cell wall–mediated resistance in wheat roots against take-all disease - Chancellor, Tania; Smith, Daniel P.; Chen, Wanxin; Clark, Suzanne J.; Venter, Eudri; Halsey, Kirstie; Carrera, Esther; McMillan, Vanessa; Canning, Gail; Armer, Victoria J.; Hammond-Kosack, Kim E.; Palma-Guerrero, Javier (Frontiers in Plant Science, 2024)
Take-all disease, caused by the Ascomycete fungus Gaeumannomyces tritici, is one of the most important root diseases of wheat worldwide. The fungus invades the roots and destroys the vascular tissue, hindering the uptake of water and nutrients. Closely related non-pathogenic species in the Magnaporthaceae family, such as Gaeumannomyces hyphopodioides, occur naturally in arable and grassland soils and have previously been reported to reduce take-all disease in field studies. However, the mechanism of take-all protection has remained unknown. Here, we demonstrate that take-all control is achieved via local but not systemic host changes in response to prior G. hyphopodioides root colonisation. A time-course wheat RNA sequencing analysis revealed extensive transcriptional reprogramming in G. hyphopodioides–colonised tissues, characterised by a striking downregulation of key cell wall–related genes, including genes encoding cellulose synthases (CESA), and xyloglucan endotransglucosylase/hydrolases (XTH). In addition, we characterise the root infection biologies of G. tritici and G. hyphopodioides in wheat. We investigate the ultrastructure of previously described “subepidermal vesicles” (SEVs), dark swollen fungal cells produced in wheat roots by non-pathogenic G. hyphopodioides, but not by pathogenic G. tritici. We show that G. hyphopodioides SEVs share key characteristics of fungal resting structures, containing a greater number of putative lipid bodies and a significantly thickened cell wall compared to infection hyphae. We hypothesise that SEVs are fungal resting structures formed due to halted hyphal growth in the root cortex, perhaps as a stress response to locally induced wheat defence responses. In the absence of take-all resistant wheat cultivars or non-virulent G. tritici strains, studying closely related non-pathogenic G. hyphopodioides provides a much needed avenue to elucidate take-all resistance mechanisms in wheat.